Examining Employees’ Perception In The Postal Department: A Comprehensive Review - Kaur, Amandeep; Aggarwal, Parmod Kumar (Gyan Management Journal, 2024)
The postal department of India fosters national integration and socio economic development by acting as a cornerstone of communication, connectivity and commerce. With the changing business scenario, practices of business organization have changed dramatically which ultimately redefines the role of employees. This review study examines employees’ perceptions within the postal department, aiming to understand the various factors that influence their perception. Through a comprehensive analysis of existing literature, including empirical studies and theoretical frameworks, the research highlights key determinants such as job satisfaction, workplace culture, reward system, management citizenship, communication, and opportunities for growth. By synthesizing these findings, the study underscores the importance of addressing these factors to enhance employee satisfaction, foster a positive work environment, and ultimately improve organizational performance within the postal sector. This abstract provides valuable insights for postal department managers and policymakers seeking to optimize employee perceptions and improve overall effectiveness in the workplace.